Central noradrenergic regulation of thyrotropin and growth hormone secretion in the rat - Jaffer, A.(Abdulla) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Med.)) -- University of Stellenbosch, 1992.